Uterine Fibroid Torsion during Pregnancy: A Case of Laparotomic Myomectomy at 18 Weeks' Gestation with Systematic Review of the Literature. (24th April 2017) - Basso, Annachiara; Catalano, Mariana Rita; Loverro, Giuseppe; Nocera, Serena; Di Naro, Edoardo; Loverro, Matteo; Natrella, Mariateresa; Mastrolia, Salvatore Andrea
Abstract : Uterine myomas are the most common benign growths affecting female reproductive system, occurring in 20–40% of women, whereas the incidence rate in pregnancy is estimated from 0.1 to 3.9%. The lower incidence in pregnancy is due to the association with infertility and low pregnancy rates and implantation rates after in vitro fertilization treatment. Uterine myomas, usually, are asymptomatic during pregnancy. However, occasionally, pedunculated fibroids torsion or other superimposed complications may cause acute abdominal pain. There are many controversies in performing myomectomy during cesarean section because of the risk of hemorrhage. Nevertheless, the majority of indication arises before labor and delivery due to acute symptoms leading to a discussion regarding the need for intervention during pregnancy. Therefore, we present a case of successful multiple laparotomic myomectomy at 17 + 2 weeks of gestational age and a systematic review of the literature in order to clarify the approach to this pathologic condition and its effect on pregnancy outcome.